Accounting for human–nature linkages in area‐based conservation monitoring through social–ecological indicator bundles - Natalie C. Ban; Mark H. Carr; Emily M. Rubidge; Anne Salomon; Joachim Claudet; Arielle Levine; Lindsay Aylesworth; Luisa Ramirez; Jenn M. Burt; Mark Andrachuk; Natascia Tamburello; Rebecca Martone; et al. (Conservation Biology, 2025)
As the coverage of area‐based conservation increases across the globe, it is critical to improve understanding of the social and ecological outcomes of such measures and the pathways to their outcomes. A social–ecological systems approach to monitoring and evaluation is increasingly advocated; yet, applications remain scarce. We sought to facilitate operationalization of this approach through prioritization of indicators when resources are scarce and to improve capture of social–ecological interactions. We convened a working group of practitioners and academics to explore linked social and ecological interactions through a case study of marine protected areas (MPAs). We used causal models (implemented through causal loop diagrams) in participatory and future‐oriented approaches to identify interactions among key nodes of the system that can be a focus of monitoring. These nodes and their interactions provided insight into linked indicators of key system components, for example, biomass, compliance, perceived legitimacy, catches, and perceived fairness. We called these indicator bundles . Indicator bundles can be applied to analyze causal modeling diagrams, identify essential elements to monitor, and inform analytical and reporting protocols. The bundles can also help identify key leverage points for adaptive management to improve outcomes of existing interventions. This approach can inform monitoring and evaluation and, ultimately, the design and adaptive management of conservation areas that maximize social and ecological benefits and minimize negative trade‐offs.